Alginate oligosaccharide alleviates D‐galactose‐induced cardiac ageing via regulating myocardial mitochondria function and integrity in mice. Issue 15 (6th July 2021) - Feng, Wenjing; Liu, Jianya; Wang, Shan; Hu, Yi; Pan, Hui; Hu, Ting; Guan, Huashi; Zhang, Dongfeng; Mao, Yongjun
Abstract: Ageing is a crucial risk factor for the development of age‐related cardiovascular diseases. Therefore, the molecular mechanisms of ageing and novel anti‐ageing interventions need to be deeply studied. Alginate oligosaccharide (AOS) possesses high pharmacological activities and beneficial effects. Our study was undertaken to investigate whether AOS could be used as an anti‐ageing drug to alleviate cardiac ageing. D‐galactose (D‐gal)‐induced C57BL/6J ageing mice were established by subcutaneous injection of D‐gal (200 mg·kg ‐1 ·d ‐1 ) for 8 weeks. AOS (50, 100 and 150 mg·kg ‐1 ·d ‐1 ) were administrated intragastrically for the last 4 weeks. As a result, AOS prevented cardiac dysfunction in D‐gal‐induced ageing mice, including partially preserved ejection fraction (EF%) and fractional shortening (FS%). AOS inhibited D‐gal‐induced up‐regulation of natriuretic peptides A (ANP), brain natriuretic peptide (BNP) and ageing markers p53 and p21 in a dose‐dependent manner. To further explore the potential mechanisms contributing to the anti‐ageing protective effect of AOS, the age‐related mitochondrial compromise was analysed. Our data indicated that AOS alleviated D‐gal‐induced cardiac ageing by improving mitochondrial biogenesis, maintaining the mitochondrial integrity and enhancing the efficient removal of impaired mitochondria. AOS also decreased the ROS production and oxidative stress status, which, in turn, further inhibiting cardiac mitochondria from being destroyed. Together, these results demonstrate that AOS may be an effective therapeutic agent to alleviate cardiac ageing.